Soil profiles from three coastal plain regions. II. Dynamics of humic substances, iron and aluminum - Gomes, João Bosco Vasconcellos; Resende, Mauro; Rezende, Sérvulo Batista de; Mendonça, Eduardo de Sá (Pesquisa Agropecuaria Brasileira, 1998)
Humic substances were characterised and Fe and Al were determined after extraction with dithionite (Fed e Ald), oxalate (Feo e Alo) e sodium pyrophosphate (Fep e Alp) for soil genesis studies from three Coastal Plain regions with different vegetation cover, in the northern Rio de Janeiro State. Lagoa do Robalo region with strong hydromorphism showed higher amounts of humic acid (HA) than fulvic acid (FA). Canto do Santo Antônio and Campos Novos regions showed decreasing HA/FA ratio with increasing soil depth. Iron concentration was very low in soil samples of the Lagoa do Robalo profile. B horizons from profiles of the Campos Novos region showed the highest levels of Fep (0.74 to 1.13 g/kg) thus confirming their morphology with red illuvial horizon. Podzolization of the profiles was more clearly observed through the trend of illuvial horizons in accumulating more pyrophosphate extractable Al than the others horizons in the same profile. Probably, the podzolization process at Lagoa do Robalo was due to migrating organic compounds. Low organic carbon/(Fep + Alp) ratio denotes a surplus of metal ions in illuvial horizons of the profiles of Canto de Santo Antônio region. At Campos Novos, Podzol profile with Bsh horizon under grassland pasture was drastically depodzolized, but it still keeps its illuvial character for organic metallic complexes.